A Study of an International College Model in the Era of Globalisation - Surawut Watana, Auayporn Apirakaramwong, Sudawadee Chanpiwat, Ariyaporn Nunthiphatprueksa , Burin T. Sriwong, Gaysorn Chansiri, (Journal of Community Development Research (Humanities and Social Sciences), 2017)
The impact of globalisation, as well as the ASEAN Economic Community, have a great influence on 21 st century learning. One of the trends of higher education, especially among countries where English is not the official language, is to offer international programmes at undergraduate and graduate levels. However, the structure of international curriculums has not been studied thoroughly. Therefore, it would be useful to examine the reasons why each institution decided to choose its structure. The research aims to shed light on a suitable model of international programme management. Based on Strategic Decision-Making Process Framework, twelve questions were created as guideline in the interviewing process. Thirty-three respondents, who are university directors, deans, vice-presidents, presidents or equivalent from twelve universities residing in Bangkok and up-country, were joined in the study. By using the semi-structure interview technique, the content analysis was applied and followed by the three-step approaches. The results showed that, even in the same country, the types of educational administration are various. The opportunities and the difficulties in managing international programmes/international college are different from one another. The international college can hardly be shaped to stereotype administration. However, the definition of internationalisation of each institution should be clear. The position of the international college or international programmes should be set since the beginning in order to better see development direction, avoid the programme administration overlapping and run efficiently in taking care of international students.
Keywords: International College, Higher Education, University, International Programme, Globalisation